Eduard Bernstein’s Reformist Revisionist Marxism - Bencomo Cuesta, Jorge (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Eduard Bernstein’s reformist revisionist Marxism, expounded mainly in the late 19th century, seeks to reinterpret classical Marxism through a reformist approach. Bernstein, a key figure in the German Social Democratic Party (SPD), proposed that socialism could be achieved through gradual reforms within capitalism, rather than violent revolution. His view contrasted with the original Marxist theory that emphasized class struggle and proletarian revolution as the necessary means to achieve social change. Bernstein rejected Marx’s materialist conception of history and economic determinism, arguing that ethical factors also played a crucial role in social evolution. Influenced by neo-Kantianism, Bernstein argued that history did not follow an exclusively economic predetermined course, but was open to the influence of ethical and moral values. Bernstein’s revisionism was criticized by Rosa Luxemburg, who defended Marx’s revolutionary theory and considered that abandoning the goal of revolution in favor of reforms within capitalism weakened the class struggle. Luxemburg asserted that proletarian emancipation could not be achieved through the use of the very structures that oppressed the workers. Despite criticism, Bernstein’s ideas gained support within the SPD, reflecting a shift toward a more legalistic and parliamentary political strategy. His revisionist approach influenced the development of social democracy and contributed to fundamental debates on the road to socialism.